Exploring the Prevalence and Predictors of Anxiety among Lithuanian Adolescents during Times of Crisis: A Cross-Sectional Study - Laura Šalčiūnaitė-Nikonovė; Monika Žemaitaitytė; Kastytis Šmigelskas (MDPI AG, 2023)
Recent events in Europe, like the COVID-19 pandemic and the 2022 Russo-Ukrainian War (RUW), might have sparked anxiety among adolescents. This study aimed to compare anxiety levels in Lithuanian adolescents post-COVID-19 peak (Study 1, October 2021) and during the onset of the RUW (Study 2, April-June 2022). Data from 459 participants in Study 1 and 6637 in Study 2, aged 11-17, were collected through HBSC pilot and national surveys in Lithuania. Self-reported questionnaires assessed anxiety, social media use, stress, loneliness, self-efficacy, and peer support factors. Analysis was conducted using multivariable logistic regressions. Notably, anxiety prevalence in Lithuanian adolescents showed no significant difference between Study 1 and Study 2, stabilizing around 24%. In 2021, stress (OR = 5.89, 95% CI 3.11-11.17), problematic social media use (OR = 4.58, 95% CI 1.89-10.58), and female gender (OR = 2.87, 95% CI 1.58-5.22) significantly predicted anxiety. By 2022, stress (OR = 3.68, 95% CI 3.14-4.30), loneliness (OR = 2.85, 95% CI 2.43-3.35), and lower self-efficacy (OR = 1.40, 95% CI 1.20-1.60) emerged as important predictors. This study enhances our understanding of adolescent anxiety during crises, emphasizing the urgency of addressing multiple factors to manage and support vulnerable youth.